Positive Cancer Experiences: Perspectives From Cancer Survivors - Fitch, Margaret I (J Patient Exp, 2020)
The purpose was to review the perspectives of cancer survivors about what they perceive constitutes positive cancer experiences. A national survey was conducted in collaboration with 10 Canadian provinces to identify experiences and unmet needs for cancer survivors between 1 and 3 years of posttreatment. The survey included open-ended questions designed to allow the respondents to add topics and details of importance. This publication presents the analysis of quantitative data and open-ended questions regarding cancer survivors’ perspectives about positive experiences and gaps in care during their cancer journey. Of the 13 534 unique adult survey respondents, 7794 (57.6%) responded to the positive experiences question and 6434 (47.5%) to the question about gaps in care. Elements of positive experiences included the compassionate health care workers, maintaining a positive outlook and the support of family and friends. Gaps in care included a lack of access to services, information, and support. Respondents were able to identify positive aspects of their cancer experiences and where improvements were needed. These findings assist in determining how health care professionals can address the needs of cancer patients based on what survivors have identified as helpful.